The added value of cardiac magnetic resonance imaging in the prevention of sudden cardiac death in athletes - Szabó, L.; Dohy, Z.; Juhász, V.; Kiss, M.; Kunze, K. P.; Merkely, B.; Vágó, H. (MAGNETOM Flash, 2022)
Early differentiation of pathological alterations from physiological cardiac adaptation in highly trained athletes is key to preventing sudden cardiac death (SCD) [1]. Athletes engaging in high training loads develop a complex electrical, volumetric adaptation to sport, known as "the athlete`s heart" [2, 3]. While not all aspects of physiological adaptation are fully understood today, many characteristics are well described. The imaging features of the athlete`s heart include a balanced elevation in left and right cavity sizes, increased myocardial mass and wall thickness, and normal or low normal systolic function at rest compared to sedentary controls [4]. The main factors contributing to the extensiveness of the morphological attributes can be categorized as physiological and pathological. The physiological factors are age, gender, ethnicity, body size, and sports discipline. The pathological factors are illegal performance-enhancing drugs and underlying heart disease [3]. Cardiac magnetic resonance (CMR) imaging is increasingly recognized as an essential second-line imaging modality to diagnose, follow-up, and informed risk stratification in several myocardial diseases such as hypertrophic or arrhythmogenic cardiomyopathy, or acute myocarditis. Recent efforts using novel techniques such as strain analysis or mapping enable more sophisticated differentiation, even in so-called "gray-zone" cases [3]. As CMR is becoming more broadly available, some initiatives have used it as a screening method in collegiate athletes after COVID-19 infection [5]. While this might not be suitable in all cases and could even lead to overdiagnosis of several entities [6], the application of CMR is undoubtedly widening. We summarize the primary applications of CMR in the context of highly trained athletes, and illustrate some real-life CMR cases using a MAGNETOM Area 1.5T MRI scanner from Siemens Healthineers.